Masseter muscle dimensions measured by ultrasound per sex - Frugone-Z., Raúl; Hernández-C., Arnoldo; Valenzuela-P., Hernán; Retamal-V., Víctor (Revista Facultad de Odontología Universidad de Antioquia, 2010)
Introduction: in order to establish the dimensions in depth, width and length of the masseter muscle according to gender, a non analytical experimental observational study was performed on selected patients who attended the echography service at the Base Hospital of Linares-Chile between July and September 2005. Methods: the sample consisted of 180 masseter muscles, 90 from female individuals and 90 from male individuals. Measurements of each masseter muscle were performed utilizing an echographic exam. ANOVA test statistical analysis was performed. Results: the masseter muscle depth on male individuals has an averaged 10.8 ± 1.6 mm and on female individuals an average depth of 8.1 ± 1.4 mm. Conclusion: according to the findings, we concluded that in male individuals with a depth of the masseter muscle higher to 12.4 mm and in female individuals with a depth of masseter higher to 9.5 mm could be considered a diagnosis of masseteric hypertrophy.